ANALISIS PENCATATAN LAPORAN KEUANGAN UMKM BERDASARKAN SAK EMKM (STANDART AKUNTANSI ENTITAS MIKRO KECIl DAN MENENGAH): STUDI KASUS PADA UMKM CV Barotech Poultry Equipment - Diana Sari; Rika Yuliastuti (Ekomania, 2023)
Micro, Small and Medium Enterprises (MSMEs) are businesses run by individuals, families and small businesses. MSMEs are usually classified based on the limitation of annual sales volume and number of employees. However, MSMEs (Micro, Small and Medium Enterprises) still face various problems related to financial reporting and financial reporting, including information containing the record of transactions that take place in a company, be it purchase or sales transactions. The purpose of this study is to understand how many financial statements are made by a resume. Barotech Poultry Equipment whether it be to include financial statements provided by the CV. Barotech Poultry Equipment complies with SAK EMKM standards and with the problems encountered when recording financial statements. This research uses a qualitative descriptio n through interviews and observations. The results of this investigation indicate that the MSME SAK has not been fully implemented in the preparation of the financial statements, and this is due to a lack of understanding of the SAK EMKM.